Bilateral and Regional Trade Agreements : Commentary and Analysis. edited by Simon Lester, Bryan Mercurio, Lorand Bartels. - Lester, Simon Nicholas; Mercurio, Bryan; Bartels, Lorand (Cambridge University Press, 2015)
The stalling of the Doha Development Round trade negotiations has resulted in bilateral and regional free trade agreements (BRTAs) becoming an important alternative. These agreements have proliferated in recent years, and now all of the major trading countries are engaging in serious bilateral trade negotiations with multiple trading partners. This second edition provides updated and comprehensive analysis of the contents and trends of recent BRTAs. It is unique in that it situates these agreements in their economic, international law and international relations contexts. It also comprehensively reviews the recent agreements in relation to each substantive topic covered (e.g. intellectual property, investment, services and social policy) so as to provide an overview of the law being created in these areas.